2014
DOI: 10.3844/ajabssp.2014.232.237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melanocortin-4 Receptor Gene on Growth and Meat Traits in Pigs Raised in Russia

Abstract: Тhe Melanocortin-4 Receptor (MC4R), a G-protein coupled receptor, is implicated in mediating the effect of leptin on food intake and energy balance. A previous candidate gene study reported an association between an MC4R polymorphism (Asp298Asn) and growth and meat productive traits of pigs. The aim of this work was to determine frequencies of the MC4R/Taq I genotypes and alleles in Danish Landrace (LD), Canadian Landrace (LC) and crossbred pigs Danish Landrace × Canadian Landrace (LD × LC) in breeding Cent "P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
10
1
2
Order By: Relevance
“…Previously research on pure-bred Landrace pigs showed a positive effect of AG/MC4R on Days to 100 kg and crossbred pigs of GG/MC4R had increased BF values (Klimenko et al, 2014). Most previous data have shown that A allelic variant of MC4R is associated with best value of Days to 100 kg, however G allele and especially GG/MC4R genotype is associated with improved BF and meat traits (Dvořáková et al, 2011;Munoz et al, 2011;Van den Broeke et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously research on pure-bred Landrace pigs showed a positive effect of AG/MC4R on Days to 100 kg and crossbred pigs of GG/MC4R had increased BF values (Klimenko et al, 2014). Most previous data have shown that A allelic variant of MC4R is associated with best value of Days to 100 kg, however G allele and especially GG/MC4R genotype is associated with improved BF and meat traits (Dvořáková et al, 2011;Munoz et al, 2011;Van den Broeke et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…The porcine MC4R gene is located on Chr 1. Several studies have investigated the impact of MC4R gene polymorphism on growth and meat traits of pigs (Kim et al, 2000;Bruun et al, 2006;Klimenko et al, 2014;Van den Broeke et al, 2015). However, the main focus of the study is the effects of MC4R gene on growth and meat traits, but there are practically no data about influence of MC4R gene polymorphisms on reproductive traits of pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Marker selection is an important trend in practical genetics (Marker Assisted Selection -MAS), suggesting the use of DNA markers associated with productivity traits [3,4]. The DNA marker-based technologies are widely applied in national breeding programs in several countries with developed sheep breeding [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…и др., которые считали, что при этом обогащается наследственность, расшатывается и ломается нежелательный наследственный консерватизм и получается приплод животных с более обогащенной и гибкой к внешним условиям наследствен ностью [8,9]. Последовательная работа спе циалистов и руководителей треста конных заводов увенчалась успехом [10].…”
Section: Introductionunclassified